Endometrial Mesenchymal Stem Cells and Their Role in the Origin and Treatment of Endometriosis - Jitong Zhao; Xiaojuan Lin; Tao Yi; An Tong; Ruyu Pi; Gang Zheng; Shuying Liao; Xia Zhao; Ce Bian; Guojuan Sun (IMR Press, 2022)
Background: To identify endometrial mesenchymal stem cells (eMSCs) in retrograde menstruation, in various endometriosis lesions, in normal control tissues, and to investigate the association between eMSCs and endometriosis. We also plan to evaluate the effect of gonadotropin-releasing hormone agonists (GnRH-a) on eMSCs. Methods: Patients diagnosed with endometriosis were included if they had experienced surgery during the time frame 1 January 2015 to 31 December 2019 in West China Second Hospital, Sichuan University. Immunofluorescence was performed to identify eMSCs in those tissues with cell surface markers PDGFR-β/CD146. The percents of eMSCs in various tissues were calculated, and compared using analysis of variance. A two-sided pvalue less than 0.05 showed significant difference. Results: This study included 508 patients. eMSCs were identified in retrograde menstruation and numerous pathologic specimen but were not detected in normal control tissues. There was no significant difference in the percent of eMSCs between the GnRH-a treatment group and the control group (p > 0.05). Conclusions: Our study demonstrated that eMSCs played a critical role in the development and recurrence of endometriosis and that GnRH-a did not affect eMSCs. Gynecologists should regard endometriosis as a chronic disease requiring lifetime management, especially for patients with chronic pelvic pain.